Incorporating Neolithic villages at Petra, Jordan: an integrated approach to sustainable tourism. Issue 2 (15th March 2017) - Tarawneh, Mohammad B.; Wray, Meredith
ABSTRACT: Listed as a World Heritage Site since 1985, the city of Petra is well regarded as the most important attraction in Jordan that is internationally recognized for its rare archaeological remains, monuments and façades that date back to Nabataean times. This paper presents an inter-disciplinary approach, which is co-constructed by an academic archaeologist and a sustainable tourism researcher that considers the integration of three rare and significant Neolithic villages as a unique extension of the cultural and heritage tourism experience in Petra. The paper begins by deliberating the implications of World Heritage Status for iconic and flagship destinations such as Petra. From this, results of a review of secondary research and interviews with local tour operators are presented which explored the issues and challenges that may inhibit the inclusion of the Neolithic villages as part of the Petra attraction system. The authors propose that an attraction diversification strategy and a sustainable tourism-planning approach are necessary to sustain the destination's long-term future, conserve Petra's archaeological sites, ensure economic benefits and appropriate participation of local communities within the region, and to serve as a way to attract more appreciative visitor markets to the region.